Development and testing of a large diameter pit digger for laterite terrain - PREMAN P.S; Er. Jippu Jacob (Guide) (Tavanur 1996 Kelappaji College of Agricultural Engineering and Technology)
Development and testing of a large diameter pit digger for laterite terrain
Development and testing of a large diameter pit digger for laterite terrain